2009
DOI: 10.1021/ac9018445
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalimide−Porphyrin Hybrid Based Ratiometric Bioimaging Probe for Hg2+: Well-Resolved Emission Spectra and Unique Specificity

Abstract: In this paper, we unveil a novel naphthalimide-porphyrin hybrid based fluorescence probe (1) for ratiometric detection of Hg(2+) in aqueous solution and living cells. The ratiometric signal change of the probe is based on a carefully predesigned molecule containing two independent Hg(2+)-sensitive fluorophores with their maximal excitation wavelengths located at the same range, which shows reversibly specific ratiometric fluorescence responses induced by Hg(2+). In the new developed sensing system, the emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(70 citation statements)
references
References 74 publications
1
68
0
1
Order By: Relevance
“…300) based on the naphthalimide chromophore and thioether-rich crown receptor as a dual signaling probe for Hg 2+ and Ag + in aqueous solution. Li et al 462 reported a novel naphthalimide-porphyrin hybrid fluorescence probe 341 (Fig. Upon introduction of mercury, a drastic change in the fluorescence take place by the 5-fold enhancement in the intensity of the emission signal with slight blue shift from 547 to 532 nm but there was no change in the absorption signal at 440 nm.…”
Section: Naphthalimide-based Hg 2+ Sensormentioning
confidence: 99%
“…300) based on the naphthalimide chromophore and thioether-rich crown receptor as a dual signaling probe for Hg 2+ and Ag + in aqueous solution. Li et al 462 reported a novel naphthalimide-porphyrin hybrid fluorescence probe 341 (Fig. Upon introduction of mercury, a drastic change in the fluorescence take place by the 5-fold enhancement in the intensity of the emission signal with slight blue shift from 547 to 532 nm but there was no change in the absorption signal at 440 nm.…”
Section: Naphthalimide-based Hg 2+ Sensormentioning
confidence: 99%
“…[9] The detection of heavy-metal ions, such as Hg 2 + ,C d 2 + ,a nd Pb 2 + are of interestf or environmental and health-related issues. [10,11] These metals are pollutantsa nd extremely toxic, therebya lteringt he biological activity of important constituents of living cells. [12][13][14][15] Other important metals, such as zinc(II), Mono-, di-, tri-, and hexaporphyrin derivatives were synthesized and their sensorial ability toward Na + ,L i + ,C a 2 + ,C u 2 + , Ni 2 + ,C o 2 + ,F e 3 + ,Z n 2 + ,C d 2 + ,H g 2 + ,A g + ,C r 3 + ,P b 2 + ,a nd Al 3 + was explored by absorption and emission spectroscopy and 1 HNMR spectroscopy.F or all of the studied porphyrin derivatives the most significant spectral changes were observed upon addition of Zn 2 + ,C d 2 + ,C u 2 + ,C o 2 + ,P b 2 + ,H g 2 + ,a nd Fe 3 + ,w hichr esulted in ac olor change from red to green.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, numerous fluorescent chemosensors and chemodosimeters have been reported in the literature 19–22. These methods may facilitate mercury analyses, even if they are only semiquantitative.…”
Section: Introductionmentioning
confidence: 99%
“…Because mercury is a soft Lewis acid, a vast majority of the chemosensors and chemodosimeters for mercury contain sulfur atom(s) that can tightly coordinate the metal as part of off-on fluorescence switches 19,21. Some of the chemosensors and chemodosimeters were successfully applied to real world “dirty” samples and in biological settings with low concentrations of mercury ions 19,22…”
Section: Introductionmentioning
confidence: 99%